Towards Si@SiO2 Core-shell, Yolk-shell, and SiO2 Hollow Structures from Si Nanoparticles through a Self-templated Etching-deposition Process. (2015) - Niu, Jin; Zhang, Su; Niu, Yue; Song, Ranran; Song, Huaihe; Chen, Xiaohong; Zhou, Jisheng; Hong, Song
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy ). This article has been retracted at the request of the Authors. The authors deeply apologize that due to their misunderstanding of the nature of the conference proceedings of WCPT7, this article became a duplicate of a paper that has already been published in RSC Adv., (2014), 4, 29435-29438. DOI: 10.1039/C4RA02236J. One of the conditions of submission of a paper for publication is that authors declare explicitly that the paper is not under consideration for publication elsewhere. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the processing of this submission.